FINANCIAL DISTRESS ASSESSMENT USING THE SPRINGATE S-SCORE MODEL: A CASE STUDY OF PT KRAKATAU STEEL TBK - Diva Fadilah; Dian Rahmania; Deva Adelia; Zahwan Pratama; Asri Sundari (Jurnal Terapan Ilmu Manajemen dan Bisnis, 2026)
Abstract This study aims to analyze the financial distress condition of PT Krakatau Steel (Persero) Tbk during 2022–2024 using the Springate S-Score model. A quantitative descriptive approach was employed using secondary data obtained from the company’s annual financial statements published by the Indonesia Stock Exchange (IDX). The analysis utilized four financial ratios in the Springate model: Working Capital to Total Assets (X₁), Earnings Before Interest and Taxes to Total Assets (X₂), Earnings Before Taxes to Current Liabilities (X₃), and Sales to Total Assets (X₄). The results show that PT Krakatau Steel (Persero) Tbk recorded S-Score values of -0.0580 in 2022, -0.3747 in 2023, and -0.4405 in 2024. All values were below the Springate cut-off point of 0.862, indicating that the company experienced financial distress throughout the observation period. This condition was mainly caused by negative working capital, low profitability, and declining asset utilization. The findings suggest the need to improve working capital management and operational efficiency. This study also provides empirical evidence of the applicability of the Springate model in assessing financial distress within a capital-intensive steel industry.   Keywords: Financial Distress, Financial Statement Analysis, Springate S-Score Model, Steel Industry